2022
DOI: 10.3389/fnut.2022.821657
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Consumption of Ultra-Processed Foods on the Maternal-Child Health: A Systematic Review

Abstract: Background and AimsChanges in eating patterns have been leading to an increase in the consumption of ultra-processed foods (UPF), negatively impacting the quality of the diet and generating risk of harm to the health of the adult population, however, there is no systematized evidence of the impact of UPF in maternal-child health. Thus, in this study we aimed to evaluated the association between UPF consumption and health outcomes in the maternal-child population.MethodsSystematic review registered on the Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 67 publications
0
22
0
2
Order By: Relevance
“…There is growing evidence that high consumption of UPFs is indicative of low diet quality and associated with a higher risk of coronary heart disease, cancer, cerebrovascular and metabolic diseases, hypertension, worse cardiometabolic risk profile, and a higher risk of all-cause mortality in adult and older populations [ 91 , 92 , 93 ]. Regarding the pregnancy period, a recent systematic review [ 27 ] indicated that high UPF consumption in pregnancy, lactation, and infancy had negative repercussions on health in general but no meta-analysis was performed. To our knowledge, this is the first study with meta-analysis to assess the effect of UPF-rich diet consumption, through unhealthy dietary patterns, Western foods and UPF intake, by pregnant women and perinatal outcomes, and is the most up-to-date and comprehensive systematic review on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that high consumption of UPFs is indicative of low diet quality and associated with a higher risk of coronary heart disease, cancer, cerebrovascular and metabolic diseases, hypertension, worse cardiometabolic risk profile, and a higher risk of all-cause mortality in adult and older populations [ 91 , 92 , 93 ]. Regarding the pregnancy period, a recent systematic review [ 27 ] indicated that high UPF consumption in pregnancy, lactation, and infancy had negative repercussions on health in general but no meta-analysis was performed. To our knowledge, this is the first study with meta-analysis to assess the effect of UPF-rich diet consumption, through unhealthy dietary patterns, Western foods and UPF intake, by pregnant women and perinatal outcomes, and is the most up-to-date and comprehensive systematic review on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review [ 27 ] reported that the highest UPF consumption negatively impacts nutrition and disease development indicators in pregnant, lactating women and children. However, a meta-analysis of the results was not conducted, and no other dietary patterns characterized by high UPF consumption were explored during the pregnancy period.…”
Section: Introductionmentioning
confidence: 99%
“…This excessive and early consumption can lead to negative effects on children's health with repercussions in adult life 21 . Although there are already studies that address the impacts of the consumption of processed foods in childhood, there is a gap in the literature of studies that assess the NP of these foods intended for and/or consumed by 0-24-month-old children 19 , which justifies the relevance of a new review on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the consumption of processed foods in childhood with excess of critical nutrients 18 (PAHO) is related to different health and nutrition outcomes, such as inadequate eating practices, poorer diet quality, excess measures and indicators of adiposity, changes in lipid profile, respiratory diseases, dental caries and even toxicity related to the ingestion of plastics present in food packaging 16,19,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation